Incidence of preeclampsia in pregnant Swiss women (Swiss Medical Weekly, 2015)
QUESTION UNDER STUDY: The epidemiology of preeclampsia in Switzerland is known only from a retrospective registry study. This analysis aimed to prospectively determine the incidence of preeclampsia in a cohort of pregnant women in Switzerland. METHODS: Pregnant women presenting at gestational week 11–14 at their obstetrician’s office were consecutively included and prospectively followed-up until the end of pregnancy. Ultrasound characteristics, blood pressure measurements, body mass index, and personal history were recorded. Duration of pregnancy, occurrence of preeclampsia, birth weight and Apgar scores were recorded as outcomes. RESULTS: There were 1,300 pregnancies with follow-up available for analysis. Median age was 30 years (interquartile range [IQR] 27–33), median body mass index (BMI) 23.3 kg/m2 (IQR 21.2–26.1), median systolic blood pressure 117 mm Hg (IQR 109–126) and median diastolic blood pressure 70 mm Hg (IQR 64–77). A total of 30 women developed preeclampsia, corresponding to an incidence of 2.31% (95% confidence interval [CI] 1.62%–3.28%). Of the women with preeclampsia, 6.66% (95% CI 2.04%–21.42%) had early-onset preeclampsia, 13.33% (95% CI 5.45%–29.83%) progressed to eclampsia, whereas 10% (95% CI 3.63%–28.75%) developed HELLP syndrome (haemolysis, elevated liver enzymes, low platelet count). Nulliparity and prior history of preeclampsia were more frequently seen in pregnancies with preeclampsia than in pregnancies without preeclampsia. BMI, as well as systolic and diastolic blood pressure were higher in pregnancies subsequently developing preeclampsia. CONCLUSION: The incidence of preeclampsia in Switzerland is in line with frequencies observed elsewhere in the world. Extrapolation to a national level indicates that about 1,911 (range 1,340–2,713) preeclampsia cases per year can be expected to occur in Switzerland.